2010
DOI: 10.1002/jat.1566
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of the differentially expressed proteins in human lung epithelial cells by airborne particulate matter

Abstract: Exposure to airborne PM₁₀, particulate matter with a median aerodynamic diameter of less than 10 µm, is known to be associated with a number of adverse health effects. To gain a better understanding of the cytotoxic mechanism and to develop protein biomarker candidates for PM₁₀-induced toxicity, proteomic analyses were performed in human lung epithelial cells. Two-dimensional gel electrophoresis (2-DE) was followed by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Studies which employ this proteomic technique have been used in experiments involving silica nanoparticles [20], multi-walled carbon nanotubes [21], titanium dioxide nanoparticles [22], airborne particulate matter [23] and silver nanoparticles [24] but there are few on AuNPs [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies which employ this proteomic technique have been used in experiments involving silica nanoparticles [20], multi-walled carbon nanotubes [21], titanium dioxide nanoparticles [22], airborne particulate matter [23] and silver nanoparticles [24] but there are few on AuNPs [25].…”
Section: Discussionmentioning
confidence: 99%
“…A number of kinases are associated with inflammatory response 52. Many studies have shown that inflammatory response is related to PM exposure 53. It has been reported that bacteria-derived endotoxin bound to the surface of PM particle is one of the causative agent in PM-mediated lung injury 5456.…”
Section: Toxic Effects Of Particulate Matter On Respiratory Systemmentioning
confidence: 99%
“…After isoelectric focusing, the strips were soaked twice for 20 min each in equilibration buffer (6 M urea, 2% w/v SDS, 20% v/v glycerol, 5 mM tributylphosphine, 2.5% acrylamide, 0.01% bromophenol blue, 0.375 M Tris-HCl, pH 8.8). The seconddimension SDS-PAGE was performed in 8Á16% gradient polyacrylamide gels without a stacking gel, at 108C for 2 h at 5 mA/gel and then at 18 mA/gel (Bartkowiak et al 2009;Choi et al 2009;Jeon et al 2011;Park et al 2010). Protein bands were visualized by staining with Coomassie Brilliant Blue G-250.…”
Section: Two-dimensional Gel Electrophoresis (2-de)mentioning
confidence: 99%